Urbanization and Condition of Urban Slums in India - Digambar Abaji Chimankar (Indonesian Journal of Geography, 2016)
The present paper attempted to study the urbanization in India and condition of urban slums in terms of water, sanitation, electricity, garbage collection and health care, and education which are supposed to be basic minimum needs for the slum dwellers. India is going through the process of rapid urbanization because of industrialization like other third world countries.  The percent of urbanization increase from 27.8 percent in 2001 to 31.1 percent in 2011 census. The increase in the percentage of population in urban areas is because of natural growth, rural to urban migration and the reclassification of village and towns. The share of the slum population in the total urban population of the country was 18.3 percent in 2001 while in 2011 it was 17.4 percent. The condition of urban slums in India is to be improved so as to make them better for living.